Open-Book Versus Closed-Book Tests in University Classes: A Field Experiment - Rummer, Ralf; Schweppe, Judith; Schwede, Annett (Frontiers in Psychology, 2019)
The present field study compares open book testing and closed book testing in two (parallel) introductory university classes in cognitive psychology. The critical manipulation concerns seven sessions of the seminars. In these sessions, all students received two questions concerning the content of the respective session. Half the participant (open book class) were allowed to use their notes and the course materials which had been distributed at the beginning of each class; the other half was not allowed to use the materials (closed book class). A surprise test conducted in the eighth week demonstrated better results for the closed book class. Further six weeks later, the final module exam took place. A number of questions asked in this exam concerned the learning matters instructed during the critical seven sessions. Even with respect to these questions, the closed book class performed better than the open book class. With respect to the other exam questions the two classes did not differ from each other. We discuss these results with respect to two possible explanations, retrieval practice and motivational aspects.